Association of the triglyceride-glucose index with all-cause and cause-specific mortality: a population-based cohort study of 3.5 million adults in ChinaResearch in context - Guangda He; Zenglei Zhang; Chunqi Wang; Wei Wang; Xueke Bai; Linkang He; Shi Chen; Guangyu Li; Yang Yang; Xiaoyan Zhang; Jianlan Cui; Wei Xu; et al. (Elsevier, 2024)
Summary: Background: The triglyceride-glucose (TyG) index has been recognized as a crucial risk factor for cardiovascular diseases. However, the association between the TyG index and mortality in the general population remains elusive. Methods: Participants were enrolled from the China Health Evaluation And risk Reduction through nationwide Teamwork (ChinaHEART), a nationwide prospective cohort study. The outcomes of interest were all-cause, cardiovascular, and cancer mortality. Restricted cubic splines and Cox regression models were used to assess the associations between the TyG index and outcomes. Findings: In total, 3,524,459 participants with a median follow-up of 4.6 (IQR, 3.1-5.8) years were included. The associations of the TyG index with all-cause and cardiovascular mortality were reverse L-shaped, with cut-off values of 9.75 for all-cause mortality and 9.85 for cardiovascular mortality. For each 1-unit increase in the TyG index, when below the cut-off values, the TyG index was not significantly associated with all-cause mortality (HR = 1.02, 95% CI: 1.00-1.03) and was only modestly associated with cardiovascular mortality (HR = 1.09, 95% CI: 1.06-1.11). Conversely, when the cut-off values were exceeded, the HRs (95% CI) were 2.10 (1.94-2.29) for all-cause mortality and 1.99 (1.72-2.30) for cardiovascular mortality. However, the association between the TyG index and cancer mortality was linearly negative (HR = 0.97, 95% CI: 0.94-0.99). Interpretation: The associations of the TyG index with all-cause and cardiovascular mortality displayed reverse L-shaped patterns, while an elevated TyG index showed a slight negative association with cancer mortality. We suggest that <9.75 could be the optimal TyG index cut-off value among the Chinese general population. Individuals at high risk of mortality might benefit from proper management of a high TyG index. Funding: The National High Level Hospital Clinical Research Funding (2023-GSP-ZD-2, 2023-GSP-RC-01), the Ministry of Finance of China and National Health Commission of China.